2020
DOI: 10.4040/jkan.20002
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Strength of Students' Self-Efficacy, Problem Solving Skills to Perform Catheter Care

Abstract: The aim of this study was to determine the predictive strength of students' self-efficacy, problem-solving skills, and other characteristics in performing intravenous practices and monitor phlebitis and infiltration. Methods: This cross-sectional study was carried out with 736 third and fourth-year students studying at the Health Sciences Faculties of Balikesir and Sakarya universities. The data were collected using the Self-Efficacy Scale, Problem-Solving Inventory and Catheter Care and Infiltration Monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…It is very important in this study that academic self-efficacy has a mediating effect on the relationship between self-directed learning and problem-solving ability, consistent with the results from Zhang et al [6]. Academic self-efficacy was significantly positively correlated with self-regulated learning, self-directed learning, and problem-solving ability, consistent with the results from other studies [6,16,31,32]. This indicates that the higher the level of a nursing student's academic self-efficacy is, the higher the level of self-regulated learning, the level of self-directed learning, and the ability to solve problems will be.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is very important in this study that academic self-efficacy has a mediating effect on the relationship between self-directed learning and problem-solving ability, consistent with the results from Zhang et al [6]. Academic self-efficacy was significantly positively correlated with self-regulated learning, self-directed learning, and problem-solving ability, consistent with the results from other studies [6,16,31,32]. This indicates that the higher the level of a nursing student's academic self-efficacy is, the higher the level of self-regulated learning, the level of self-directed learning, and the ability to solve problems will be.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that the higher the level of self-directed learning of a nursing student is, the higher their problem-solving ability will be; problem-solving ability was promoted by facilitating self-directed learning. This finding supports the previous findings [6,16]. Self-directed learning helps motivate the search for new data to evaluate and modify results achieved in the reflective judgment process [2,31].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Self-efficacy may have protected the students from the negative effects of anxiety with respect to their academic performance [ 46 ], and may have partially mediated the relationship, which demonstrated that higher stress levels affected poorer academic performance during exams [ 47 ]. Particularly, higher self-efficacy was positively correlated with nursing students correctly performing cardiac compression skills [ 48 ], catheter care, and infiltration monitoring [ 49 ]. Although whether the emotions are negative or positive during specific situations does not completely affect the outcomes, the ways in which students manage their emotions could have an impact on the outcomes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%